Fakultas Peternakan, Universitas Mataram, Nusa Tenggara Barat 83125 Telephon 633603 - KARDA, I W. (Majalah Ilmiah Peternakan; Vol 10 No 2 (2007), 2012)
ABSTRACT This experiment was conducted to assess the intake and digestibility of low quality rhodes grass (Chloris gayana) hay cv. Callide offered to sheep. Four rumen fistulated sheep were assigned to four dietary treatments with 21 days for each period namely, rhodes grass hay was fed alone ad lib. (treatment 1), rhodes grass hay was supplemented with 200 g/d oven-dried leucaena (treatment 2), rhodes grass hay was supplemented with 200 g/d leucaena plus 8 g/d urea (treatment 3) and rhodes grass hay was suplemented with 200 g/d leucaena plus 150 g/d sucrose (treatment 4). This experiment used a latin square design and variables measured were dry matter, organic matter intake and digestibilities of OM, NDF and N by the method of total collection, N balance, ruminal parameters such as rumen pH and ammonia, and rumen microbial protein synthesis. Differences between means were analysed by the General Linear Model procedure of the Statistical Analysis System. The results showed that although leucaena supplementation increased total DM intake total OM and digestible OM intake did not change. Supplementation increased ammonia-N concentration, N balance and efficiency of microbial N synthesis, especially with urea (P<0.05). It can be concluded that leucaena supplementation of 16% of DMI may need additional N source such as urea for better microbial N synthesis, however the need for ruminally fermentable organic matter may not be required unless rumen ammonia-N is not limiting.